Fluxes of greenhouse gases from Andosols under coffee in monoculture or shaded by Inga densiflora in Costa Rica - Hergoualc'h, Kristell; Skiba, U.; Harmand, J.M.; Henault, C. (2008)
The objective of this study was to evaluate the effect of N fertilization and the presence of N2 fixing leguminous trees on soil fluxes of greenhouse gases. For a one year period, we measured soil fluxes of nitrous oxide (N2O), carbon dioxide (CO2) and methane (CH4), related soil parameters (temperature, water-filled pore space, mineral nitrogen content, N mineralization potential) and litterfall in two highly fertilized (250 kg N ha-1 year-1) coffee cultivation: a monoculture (CM) and a culture shaded by the N2 fixing legume species Inga densiflora (CIn). Nitrogen fertilizer addition significantly influenced N2O emissions with 84% of the annual N2O emitted during the post fertilization periods, and temporarily increased soil respiration and decreased CH4 uptakes. The higher annual N2O emissions from the shaded plantation (5.8 ± 0.3 kg N ha-1 year-1) when compared to that from the monoculture (4.3 ± 0.1 kg N ha-1 year-1) was related to the higher N input through litterfall (246 ± 16 kg N ha-1 year-1) and higher potential soil N mineralization rate (3.7 ± 0.2 mg N kg-1 d.w. d-1) in the shaded cultivation when compared to the monoculture (153 ± 6.8 kg N ha-1 year-1 and 2.2 ± 0.2 mg N kg-1 d.w. d-1). This confirms that the presence of N2 fixing shade trees can increase N2O emissions. Annual CO2 and CH4 fluxes of both systems were similar (8.4 ± 2.6 and 7.5 ± 2.3 t C-CO2 ha-1 year-1, -1.1 ± 1.5 and 3.3 ± 1.1 kg C-CH4 ha-1 year-1, respectively in the CIn and CM plantations) but, unexpectedly increased during the dry season.